PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN HASIL PEMBELAJARAN TEMATIK TEMA PERTUMBUHAN DAN PERKEMBANGAN MAKHLUK HIDUP PADA SISWA KELAS III SDN 4 SUKAJAWA BANDAR LAMPUNG TAHUN PELAJARAN 2018/2019 - Siti Kholipatun (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
Based on preliminary observations at SDN 4 Sukajawa, there were problems in learning in grade III. The learning process is centered on the teacher, the learning model used by the teacher has not been varied and tends to be monotonous, the teacher has not taught students in groups, students do not do group activities and tend to be noisy when learning takes place. So it has an impact on low student learning outcomes with 41.67% classical completeness. Based on these problems, the solution chosen is to apply the Talking Stick type of cooperative learning model, because this learning model is a group learning model that can increase student activity. The formulation of the general problem of this research is whether the application of the Talking Stick type of cooperative learning model can improve the quality of Thematic learning in the Themes of Growth and Development of Living Things for Class III SDN 4 Sukajawa students. Whereas specifically, whether the Talking Stick type of cooperative learning model can improve teacher skills, student activities, and student learning outcomes in Thematic learning of the Themes of Growth and Development of Living Things in SDN 4 Sukajawa? The purpose of this study was to improve the quality of learning including teacher skills, student activities and thematic learning outcomes of the theme of growth and development of living beings for grade III SDN 4 Sukajawa students. This type of research is a classroom action research with two cycles. Each cycle consists of four stages, namely planning, implementing, observing, and reflecting. The research subjects were third grade students of SDN 4 Sukajawa. The data collection technique used tests, and observations / observations. The results showed the skills of the first cycle teachers to score 36 good criteria. In cycle II obtained a score of 45 with very good criteria. The activity of the first cycle students obtained an average score of 58.8 with good criteria. Cycle II increased with an average score of 65.6 with very good criteria. Completeness of classical learning cycle I was 66.67%, cycle II increased to 87.5%.